COMPETITIVE ENVIRONMENT AND MYOPIA PROGRESSION IN YOUNG PEOPLE: A PROSPECTIVE STUDY - SINGH, POOJA; CHOUDHARY, PANKAJ; LAKHTAKIA, SUJATA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Purpose: The aim of the study was to determine the effect of duration and distance of reading and writing over myopia progression in young people. Methods: This prospective, observational, and single-centered study was conducted on 400 eyes of 200 myopic patients. Eyes were categorized into three groups based on degree of myopia (low, moderate, and high) at the time of presentation. Cycloplegic autorefraction followed by subjective refinement of refraction was done and spherical equivalent (SE) was calculated at baseline (Time 1), and then after 6 months (Time 2), and at 1 year (Time 3). Progression of myopia was calculated as increase in SE of subject’s eye between Time 1 and Time 3. Questionnaire survey about the amount of time spent on reading and writing and their preferred working distance in centimeters for each task was filled. Task specific diopter hours per day was calculated. Multivariate analysis was done to estimate the adjusted odds ratio for time spent on reading and writing and their preferred working distance in centimeters for each task and task specific diopter hours per day for reading and writing associated with myopia progression was calculated. Results: Mean task specific reading and writing diopter hours per day in eyes with progression was 40±12 whereas that in eyes with no progression was 30±10. The observed difference was statistically highly significant (p<0.01). Task specific reading and writing diopter hours per day was significantly higher in eyes with progression as compared to no progression in low and moderate as well as in high myopes (p<0.01). Conclusion: Risk of progression of myopia was significantly (<0.05) higher in patients engaged in longer duration of reading and writing (>6 h) and at near distance (<25 cm).